Pengaruh Pendapatan Petani Terhadap Biaya Pendidikan Anak Usia Sekolah Kecamatan Nangaroro Kabupaten Nagekeo - Beatrix Wea; Damianus Tola (Program Studi Pendidikan Ekonomi, Universitas Flores, 2016)
This study aims to determine: Income of farmers, and Effect of income level of farmers to the education of children in the village Ulupulu Nangaroro district in Nagekeo Regency. The approach used is a quantitative approach. The independent variables in this study were farmers' income (x) and the dependent variable is education (y). The samples are 50 farmers in the village Ulupulu Nangaroro district in Nagekeo Regency. The analysis showed that the average income of the parents of more than 2.000.000 million Rupiah. Income parents heve a value of correlation rxy = 0,3887, it indicates there is an influence of income on the level of education of children.